AMSER National Medical Student Curriculum in Radiology (Out of Print) - Petra Lewis; Kitt Shaffer (Association of American Medical Colleges, 2010)
Abstract This resource for medical students is a 4-year curriculum covering modality/specialty-specific areas that they should be exposed to. It includes anatomy, radiology pathology, risks, and imaging algorithms within each area, as well as curriculum resources, web-links, suggestions for implementation, example goals, and the "must see" image shortlist. It is designed for the general medical student population (i.e. not specifically those going into radiology). It is not designed for any one particular clerkship or elective period, but can be adapted depending on the resources and time available. This curriculum was initially developed in 2005 and is still the only national comprehensive curriculum for medical students learning radiology. It has been used in whole or part by multiple Alliance of Medical Student Educators in Radiology members and others to develop or improve their curricula. Three presentations at the 2009 Association of University Radiologist meeting referenced this curriculum. The "must see" list has been adopted by several student educators to make electronic resources of various types.